2004
DOI: 10.1161/01.cir.0000143632.06471.93
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase Activation Mediates Ischemic Preconditioning in Murine Heart

Abstract: Background-Phosphorylation of sphingosine by sphingosine kinase (SK) is the rate-limiting step in the cellular synthesis of sphingosine 1-phosphate (S1P). The monoganglioside GM 1 , which stimulates SK, is cardioprotective in part through increased generation of S1P that protects myocytes by diverse mechanisms. Because protein kinase C (PKC)⑀ activation is necessary for myocardial ischemic preconditioning (IPC) and PKC activators increase SK activity, we tested the hypothesis that SK may be a central mediator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 44 publications
10
136
0
Order By: Relevance
“…To functionally neutralize the excessive levels of ceramide in the lung, we aimed to upregulate S1P signaling. S1P levels are regulated by three groups of enzymes: sphingosine kinase-1 and -2, which phosphorylate sphingosine to S1P, being the major enzymes involved in S1P synthesis (9,28,36); S1P lyase (37); and sphingosine phosphate phosphatases and lipid phosphate phosphatase-1 (11), which are involved in prompt S1P breakdown. Our studies indicate that VEGFR blockade does not inhibit SphK-1 activity and does not down-regulate S1P levels in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To functionally neutralize the excessive levels of ceramide in the lung, we aimed to upregulate S1P signaling. S1P levels are regulated by three groups of enzymes: sphingosine kinase-1 and -2, which phosphorylate sphingosine to S1P, being the major enzymes involved in S1P synthesis (9,28,36); S1P lyase (37); and sphingosine phosphate phosphatases and lipid phosphate phosphatase-1 (11), which are involved in prompt S1P breakdown. Our studies indicate that VEGFR blockade does not inhibit SphK-1 activity and does not down-regulate S1P levels in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Lungs from DC101-and MF1-or SU5416-treated mice and their respective controls were homogenized via microultrasonic cell disrupter in assay buffer (9), followed by centrifugation at 100,000 3 g for 20 minutes (28). SphK1 activity was measured in the supernatant, using D-sphingosine-coated phospholipid FlashPlates (PerkinElmer Life Sciences, Waltham, MA), as described in detail in the online supplement.…”
Section: Determination Of Sphingosine Kinase-1 Enzymatic Activitymentioning
confidence: 99%
“…Indeed, S1P preincubation has been shown to prevent mortality induced by hypoxia [67,68]. S1P has independently been shown to positively influence cardiac cell survival and is enhanced during ischemic periods [69].…”
Section: Ceramide and Reactive Oxygen Speciesmentioning
confidence: 99%
“…Jin et al [24] have shown that the cardioprotection conferred by the monoganglioside GM-1, which stimulates SK, is cardioprotective in part through increased generation of S1P. They have also shown that the cardioprotection conferred by myocardial ischemic preconditioning may also be mediated through PKCε mediated increase in SK activity [40]. Furthermore, Theilmier et al [41] have also shown that intravenous administration of S1P 30 min prior to ischemia reduces myocardial injury in an in vivo model of myocardial I/R injury.…”
Section: Sphingolipids and Myocardial I/r Injurymentioning
confidence: 99%
“…It is a competitive inhibitor of SK and is widely used in experimental studies [45]. Previously Jin et al [40] have shown that high dose DMS inhibits the cardioprotection observed in ischemic preconditioning through inhibition of SK via inhibition of PKCε activity in isolated murine hearts. However, subsequent experiments demonstrated that DMS has a biphasic effect on cardioprotection and while a high dose of DMS is inhibitory, low dose DMS protects murine hearts against myocardial I/R injury via activation of PKCε-SK-S1P-Akt pathway [46].…”
Section: Sphingolipids and Myocardial I/r Injurymentioning
confidence: 99%